Collaborative Governance Guna Efektivitas Pemerintahan Kelurahan Sengkuang Kecamatan Sintang - Hahury, Jhony Fredy (Universitas Kapuas Sintang, 2025)
Abstract: his study aims to analyse collaborative governance for government effectiveness in Sengkuang Village, Sintang District. By using qualitative descriptive method. The results showed that collaborative governance in Sengkuang Village has a positive impact on government effectiveness. The active involvement of the community, in this case community leaders, Karang Taruna, RT / RW and other parties, is certainly able to strengthen governance through village deliberations, meetings, and musrenbang as a commitment to the success of governance. The effectiveness and quality of public services help improve government efficiency and accountability to strengthen good and responsible governance. The importance of the role of collaborative governance in improving the effectiveness of village governance, as a collaboration that creates public trust in the village government. Keywords: Collaborative Governance, Government Effectiveness.